A production process of ultra-white glaze ceramic tile
Through multi-layered structural design and material selection, the problem of insufficient whiteness and gloss in ultra-white glazed tiles has been solved, achieving efficient light reflection and transparency, and improving the durability and service life of the tiles.
Patent Information
- Application Number
- CN202411556574.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-04
AI Technical Summary
Existing ultra-white glazed ceramic tiles lack sufficient whiteness and gloss, and the traditional materials have a low refractive index, resulting in poor light reflection and refraction effects.
It adopts a multi-layer structure design, including a base layer, a functional layer and a protective layer. It uses barium titanate with a high refractive index as the bottom layer, microcrystalline glass containing titanium dioxide as the middle layer, and nanoparticles doped with rare earth elements as the surface layer. Combined with excellent material selection and heat treatment process, it enhances light reflection and transparency.
It improves the whiteness, gloss and reflectivity of the tiles, enhances their wear resistance, corrosion resistance and weather resistance, and reduces production costs.
Smart Images

Figure CN119059841B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic building materials, and in particular to a production process of ultra-white glaze ceramic tiles. Background Art
[0002] Super white glazed ceramic tile is a ceramic tile made by a special process, which is characterized by high whiteness, glossiness and excellent physical and chemical properties. This kind of ceramic tile has been widely used in the field of architectural decoration due to its unique aesthetic effect and durability. The production process of super white glazed ceramic tile ensures that the ceramic tile has very high whiteness, excellent glossiness and excellent physical and chemical properties through the selection and proportioning of various raw materials and strict process control, so as to produce super white glazed ceramic tiles with excellent performance to meet the market demand for high-quality building materials.
[0003] However, existing ultra-white glazed tiles still have the problem of insufficient whiteness and glossiness. The materials commonly used in traditional white glaze, such as quartz, feldspar, kaolin, etc., have a low refractive index, which makes the number of reflections of light in the material less, and cannot achieve efficient reflection effect. In addition, the refractive index of the ultra-white glaze material does not match the refractive index of other layers, resulting in poor reflection and refraction effects between different layers, thereby reducing the final whiteness and glossiness. Therefore, a production process for ultra-white glazed tiles is needed to solve the above problems. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide a production process for ultra-white glaze tiles.
[0005] A production process of ultra-white glaze ceramic tiles comprises the following steps:
[0006] (1) Preparation of base layer: The raw materials of the base layer include kaolin, quartz sand and feldspar; the raw materials of the base layer are mixed evenly; a hydraulic press is used to press the mixed raw materials to form a base layer body; the pressed body is naturally dried for 24 hours; the dried body is preliminarily sintered to obtain a base tile;
[0007] (2) Functional layer preparation: The functional layer materials include barium titanate, glass-ceramics containing titanium dioxide, and nanoparticles doped with rare earth elements;
[0008] Mix barium titanate powder with water to form a slurry, and apply a layer of slurry on the base tile by brushing, with a thickness of 0.5mm;
[0009] Mix the titanium dioxide-containing glass-ceramic powder with water to form a uniform slurry, and apply it on the bottom layer by scraping to form an intermediate layer with a thickness of 1 mm;
[0010] The rare earth element-doped nanoparticles were mixed with water to form a uniform slurry, and a surface layer was formed on the intermediate layer by doctor blade coating with a thickness of 0.3 mm;
[0011] The coated tiles are naturally dried for 24 hours; the dried tiles are subjected to secondary sintering to obtain functional tiles;
[0012] (3) Preparation of protective layer: The protective layer material includes polyurethane coating; the polyurethane coating is mixed with a thinner evenly; the prepared coating is sprayed evenly on the surface of the tile with a thickness of 0.1 mm using a spray gun; the sprayed tile is naturally dried for 24 hours or accelerated curing to obtain an ultra-white glazed tile.
[0013] Preferably, the base layer raw materials are mixed in a mass ratio of 50% kaolin, 30% quartz sand and 20% feldspar.
[0014] Preferably, the preliminary sintering is carried out at a temperature of 1000-1200° C. for 2 hours.
[0015] Preferably, the titanium dioxide-containing microcrystalline glass is formed by adding titanium dioxide to glass raw materials and performing heat treatment and crystallization at 800-1000°C. The glass raw materials include silicate (SiO2), alkali metal oxides (Na2O, K2O), calcium magnesium oxides (CaO, MgO), a clarifier and a decolorizer. The clarifier includes sodium nitrate and ammonium nitrate (NH4NO3), and the decolorizer includes sodium selenite.
[0016] Preferably, the particle size of the titanium dioxide-containing glass-ceramics is 5-20 microns.
[0017] Preferably, the rare earth element-doped nanoparticles are yttrium-doped aluminum oxide (Al2O3:Y).
[0018] Preferably, in the functional layer material, barium titanate accounts for 20%-30% of the total functional layer material mass, and the mass ratio of barium titanate powder to water is 1:0.3 to 1:0.5; microcrystalline glass containing titanium dioxide accounts for 40%-50% of the total functional layer material mass, and the mass ratio of microcrystalline glass powder containing titanium dioxide to water is 1:0.4 to 1:0.6; nanoparticles doped with rare earth elements account for 10%-20% of the total functional layer material mass, and the mass ratio of nanoparticles doped with rare earth elements to water is 1:0.2 to 1:0.4.
[0019] Preferably, the secondary sintering is carried out at a temperature of 1100-1300° C. for 3 hours.
[0020] Preferably, the polyurethane coating is a polyurethane varnish, including a polyester polyurethane coating or an aliphatic polyurethane coating.
[0021] Preferably, the accelerated curing temperature is 80° C. and the time is 1 hour.
[0022] Detailed description of the above solution:
[0023] 1. Base layer: Select silicate ceramic substrate with good mechanical properties and chemical stability as the basic supporting layer of tiles to provide the necessary hardness and durability.
[0024] 2. Functional layer: Barium titanate (BaTiO3) has a high refractive index and good optical properties. As the bottom layer, it can effectively enhance the reflectivity of light; microcrystalline glass containing titanium dioxide is used as the middle layer. Due to its excellent optical transparency and high refractive index, it can further enhance the multiple reflections of light, making the surface of the tile smoother and more delicate; yttrium-doped alumina (Al2O3:Y) nanoparticles have extremely high hardness and chemical stability. As the surface layer, it can not only improve the wear resistance and corrosion resistance of the tile, but also reduce light scattering through its small size, making the light more evenly distributed on the surface of the tile, thereby improving the visual effect of the tile.
[0025] In addition, the bonding between barium titanate and the base layer mainly depends on the intermolecular van der Waals force and electrostatic force, the bonding between microcrystalline glass and barium titanate also depends on the intermolecular force, and the bonding between yttrium-doped aluminum oxide nanoparticles and microcrystalline glass mainly depends on physical adsorption and chemical bonding. During the high-temperature sintering process, a certain degree of diffusion will occur at the interface of each layer, which can enhance the bonding between the layers and reduce the stratification phenomenon. In addition, the crystal structure of barium titanate matches the crystallization structure of microcrystalline glass, which can reduce the stress concentration at the interface and thus enhance the bonding force.
[0026] In general, through refractive index matching, the bottom layer of barium titanate reflects light, the middle layer of microcrystalline glass enhances light transmittance, and the nanoparticles reduce light scattering, which together improve the optical properties of the tile. The multi-layer hardness gradient design gradually increases from the bottom layer to the surface layer, which can improve the overall mechanical strength of the tile and reduce the crack propagation caused by local stress concentration. Yttrium-doped aluminum oxide nanoparticles have excellent chemical stability, can resist erosion by corrosive substances such as acids and alkalis, and extend the service life of the tile. At the same time, microcrystalline glass has good weather resistance and can resist ultraviolet radiation and climate change, further improving the long-term durability of the tile.
[0027] 3. Protective layer: Use an organic coating (polyurethane) with high transparency and good chemical stability to protect the functional layer from the influence of the external environment and extend the service life of the tile.
[0028] The technical solution provided by the present invention includes the following beneficial effects: 1. The present invention improves the whiteness, glossiness and reflectivity of the ceramic tile by producing an ultra-white glaze ceramic tile with a multi-layer structure and optimizing the microstructure, material selection and manufacturing process of the ceramic tile; the multi-layer structure of the ceramic tile includes a base layer, a functional layer and a protective layer, and each layer uses different materials, wherein the functional material is used in the middle layer of the ceramic tile, and the reflectivity of the ceramic tile is improved by using barium titanate with a high refractive index as the bottom layer, and a microporous structure material with light scattering characteristics (microcrystalline glass containing titanium dioxide) is introduced as the middle layer to form a porous structure to enhance the scattering effect of light, and a material with a high refractive index and a high birefringence (aluminum oxide nanoparticles doped with yttrium) is used as the surface layer to enhance the glossiness and transparency of the ceramic tile surface.
[0029] 2. The present invention can improve the durability and service life of ceramic tiles through reasonable material selection and heat treatment process. The yttrium-doped aluminum oxide nanoparticles have extremely high hardness, which enhances the wear resistance of the ceramic tiles. The barium titanate and microcrystalline glass have good chemical stability, which enhances the corrosion resistance of the ceramic tiles. The yttrium-doped aluminum oxide nanoparticles have excellent chemical stability and UV resistance, which improves the weather resistance of the ceramic tiles.
[0030] 3. The present invention reduces production costs by selecting low-cost materials, through reasonable design and manufacturing processes, and adopting traditional dry pressing and sintering processes. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The figure is a schematic diagram of the production process of the ultra-white glaze ceramic tile adopted in the present invention. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Description of some materials used in the following examples:
[0034] ① Titanium dioxide-containing microcrystalline glass is formed by adding titanium dioxide to glass raw materials and performing heat treatment and crystallization at 800-1000°C. The glass raw materials include silicate (SiO2), alkali metal oxides (Na2O, K2O), calcium magnesium oxides (CaO, MgO), clarifiers and decolorizers. The clarifiers include sodium nitrate (NaNO3) and ammonium nitrate (NH4NO3). The decolorizers include sodium selenite (Na2SeO3). The particle size of the titanium dioxide-containing microcrystalline glass used is 5-20 microns.
[0035] ② Yttrium-doped alumina (Al2O3:Y) is a type of aluminum oxide nanoparticles doped with yttrium, with a particle size of 5-20 nanometers.
[0036] ③ The polyurethane coating is a polyurethane varnish, including a polyester polyurethane coating or an aliphatic polyurethane coating. The embodiments uniformly use polyester polyurethane coating.
[0037] Embodiment 1: A production process of ultra-white glaze ceramic tiles, such as Figure 1 As shown, the following steps are included:
[0038] (1) Preparation of base layer: 50% kaolin, 30% quartz sand and 20% feldspar are mixed evenly by mass percentage; the mixed raw materials are pressed by a hydraulic press to form a base layer body; the pressed body is naturally dried for 24 hours; the dried body is preliminarily sintered at a temperature of 1000°C for 2 hours to obtain a base tile;
[0039] (2) Preparation of functional layer: By mass percentage, the functional layer material includes 25% barium titanate, 45% microcrystalline glass containing titanium dioxide, and 15% yttrium-doped aluminum oxide;
[0040] Mix barium titanate powder and water in a mass ratio of 1:0.3 to form a slurry, and apply a layer on the base tile by brushing to form a base layer with a thickness of 0.5 mm;
[0041] The titanium dioxide-containing glass-ceramic powder was mixed with water in a mass ratio of 1:0.4 to form a uniform slurry, and an intermediate layer was formed on the bottom layer by scraping with a thickness of 1 mm;
[0042] The rare earth element-doped nanoparticles and water were mixed at a mass ratio of 1:0.2 to form a uniform slurry, and a surface layer was formed on the middle layer by scraping with a thickness of 0.3 mm;
[0043] The coated tiles are naturally dried for 24 hours; after drying, they are secondary sintered at a temperature of 1100°C for 3 hours to obtain functional tiles;
[0044] (3) Preparation of protective layer: Mix the polyurethane coating and the diluent evenly; use a spray gun to evenly spray the prepared coating on the surface of the tile with a thickness of 0.1 mm; let the sprayed tile dry naturally for 24 hours to obtain ultra-white glazed tiles.
[0045] Embodiment 2: A production process of ultra-white glaze ceramic tiles, such as Figure 1 As shown, the following steps are included:
[0046] (1) Preparation of base layer: The base layer raw materials are mixed evenly according to the mass ratio of kaolin 50%, quartz sand 30%, and feldspar 20%; the mixed raw materials are pressed using a hydraulic press to form a base layer body; the pressed body is naturally dried for 24 hours; the dried body is preliminarily sintered at a temperature of 1100°C for 2 hours to obtain a base tile;
[0047] (2) Preparation of functional layer: By mass percentage, the functional layer material includes 22% barium titanate, 50% microcrystalline glass containing titanium dioxide, and 10% yttrium-doped aluminum oxide;
[0048] Mix barium titanate powder and water in a mass ratio of 1:0.4 to form a slurry, and apply a layer of slurry on the base tile by brushing to form a base layer with a thickness of 0.5 mm;
[0049] The titanium dioxide-containing glass-ceramic powder was mixed with water in a mass ratio of 1:0.5 to form a uniform slurry, and an intermediate layer was formed on the bottom layer by scraping, with a thickness of 1 mm;
[0050] The rare earth element-doped nanoparticles and water were mixed at a mass ratio of 1:0.3 to form a uniform slurry, and a surface layer was formed on the middle layer by scraping with a thickness of 0.3 mm;
[0051] The coated tiles are dried naturally for 24 hours; the dried tiles are sintered for a second time at a temperature of 1200°C for 3 hours to obtain functional tiles;
[0052] (3) Preparation of protective layer: Mix the polyurethane coating and the diluent evenly; use a spray gun to evenly spray the prepared coating on the surface of the tile with a thickness of 0.1 mm; accelerate the curing of the sprayed tile at a temperature of 80°C for 1 hour to obtain an ultra-white glazed tile.
[0053] Embodiment 3: A production process of ultra-white glaze ceramic tiles, such as Figure 1 As shown, the following steps are included:
[0054] (1) Preparation of base layer: The base layer raw materials are mixed evenly according to the mass ratio of kaolin 50%, quartz sand 30%, and feldspar 20%; the mixed raw materials are pressed using a hydraulic press to form a base layer body; the pressed body is naturally dried for 24 hours; the dried body is preliminarily sintered at a temperature of 1200°C for 2 hours to obtain a base tile;
[0055] (2) Preparation of functional layer: By mass percentage, the functional layer material includes 30% barium titanate, 40% microcrystalline glass containing titanium dioxide, and 12% yttrium-doped aluminum oxide;
[0056] Mix barium titanate powder and water in a mass ratio of 1:0.5 to form a slurry, and apply a layer of 0.5mm thick on the base tile by brushing;
[0057] The titanium dioxide-containing glass-ceramic powder was mixed with water in a mass ratio of 1:0.6 to form a uniform slurry, and an intermediate layer was formed on the bottom layer by scraping with a thickness of 1 mm;
[0058] The rare earth element-doped nanoparticles and water were mixed at a mass ratio of 1:0.4 to form a uniform slurry, and a surface layer was formed on the middle layer by doctor blade coating with a thickness of 0.3 mm;
[0059] The coated tiles are naturally dried for 24 hours; the dried tiles are secondary sintered at a temperature of 1300°C for 3 hours to obtain functional tiles;
[0060] (3) Preparation of protective layer: Mix the polyurethane coating and the diluent evenly; use a spray gun to evenly spray the prepared coating on the surface of the tile with a thickness of 0.1 mm; let the sprayed tile dry naturally for 24 hours to obtain ultra-white glazed tiles.
[0061] Comparative Example: A conventional production process of ultra-white glaze ceramic tiles, comprising the following steps:
[0062] (1) Slurry preparation: Mix 40% clay, 30% quartz sand, 20% feldspar, 5% talc and 5% dolomite evenly by mass percentage, and add 30% water of the raw materials to make slurry;
[0063] (2) Pressing: Use a hydraulic press to press the mud into bricks, the pressing pressure is 20MPa, and the brick thickness is 10mm;
[0064] (3) Drying: Place the pressed bricks in a well-ventilated environment to dry naturally for 24 hours;
[0065] (4) First firing: The dried bricks are sent into the kiln for preliminary sintering at a temperature of 1100°C for 2 hours;
[0066] (5) Glazing: According to the mass percentage, 40% of feldspar, 30% of quartz, 20% of clay, 5% of zinc oxide and 5% of lead oxide are mixed evenly, and 40% of water is added to the total amount of raw materials to make a white glaze, and the white glaze is evenly applied on the surface of the fired brick;
[0067] (6) Second firing: The glazed tiles are sent into the kiln for secondary sintering at a temperature of 1200°C for 3 hours to produce ultra-white glazed tiles.
[0068] Performance testing: The ultra-white glaze tiles of Examples 1 to 3 and the comparative example were subjected to relevant performance tests, including whiteness, glossiness, reflectivity, wear resistance, corrosion resistance, and weather resistance;
[0069] 1. Whiteness test: According to GB / T 5713-2009 "Test methods for ceramic tiles Part 2: Determination of water absorption, apparent porosity, apparent relative density and bulk density", clean the sample surface to ensure that there is no stain, use a whiteness meter to measure the whiteness value of the sample, record and analyze the data, and the whiteness value should meet the predetermined standard, that is, ≥85%.
[0070] 2. Gloss test: According to GB / T 13452.2-2008 "Determination of gloss of paint and varnish films"
[0071] Clean the sample surface to ensure there is no stain. Use a gloss meter to measure the gloss value of the sample (measured at an angle of 60°) at room temperature of 20±2℃ and relative humidity of 50±5%. Record and analyze the data. The gloss value should meet the predetermined standard, i.e. ≥80GU.
[0072] 3. Reflectivity test: According to GB / T 13452.3-2008 "Determination of reflectivity of paint and varnish films", clean the sample surface to ensure that there is no stain, use a spectrometer to measure the reflectivity of the sample at different wavelengths (400nm, 500nm and 700nm), record and analyze the data, and the average reflectivity should be within the predetermined range, that is, ≥90%.
[0073] 4. Wear resistance test: According to GB / T 3810.7-2016 "Test methods for ceramic tiles Part 7: Determination of wear resistance", fix the sample on the wear resistance testing machine, use the specified grinding wheel to carry out the wear test (1000 revolutions) under the specified conditions, observe and record the changes on the sample surface, record and analyze the data, and there should be no obvious scratches or damage on the surface after wear.
[0074] 5. Corrosion resistance test: According to JC / T 798-2013 "Test method for chemical corrosion resistance of building sanitary ceramic products", place the sample in a corrosion test box, use the specified corrosive medium (5% NaCl solution) to carry out corrosion test under specified conditions (72 hours), observe and record the changes on the sample surface, record and analyze the data, and there should be no obvious corrosion spots or damage on the surface after corrosion.
[0075] 6. Weathering test: According to GB / T 1522-2007 "Determination of Weathering Resistance of Paint Film", place the sample in an artificial weathering chamber and conduct a weathering test (500 hours) under the specified climatic conditions (ultraviolet irradiation: 1.0 W / m² / nm @ 340nm, 8 hours of irradiation and 16 hours of darkness; rainwater scouring: spraying for 10 minutes each time, spraying once every 4 hours, water temperature 40°C), observe and record the changes on the sample surface, record and analyze the data, and there should be no obvious fading or damage on the sample surface after the weathering test.
[0076] As can be seen from Table 1, Example 1, Example 2 and Example 3 all performed excellently in terms of whiteness, glossiness and reflectivity, and all indicators exceeded the predetermined standards, showing higher optical properties, while the comparative example was slightly inferior in terms of optical properties.
[0077] Table 1 Test results of whiteness, glossiness and reflectivity of ultra-white glaze tiles
[0078] Test items Whiteness value (%) Gloss value (GU) Average reflectivity (%) Example 1 92 90 95 Example 2 90 88 93 Example 3 93 92 96 Comparative Example 86 82 88
[0079] As can be seen from Table 2, Example 1, Example 2 and Example 3 perform well in terms of wear resistance, and their wear resistance is better than that of the comparative example. The wear resistance of the comparative example is relatively weak, and slight scratches appear on the surface after the test.
[0080] Embodiment 1, embodiment 2 and embodiment 3 all perform well in corrosion resistance and weather resistance, and are able to resist chemical corrosion and the influence of adverse climatic conditions. The comparative example is slightly inferior in corrosion resistance and weather resistance, and slight corrosion spots and fading appear on the surface after the test.
[0081] Table 2 Test results of wear resistance, corrosion resistance and weather resistance of ultra-white glaze tiles
[0082] Test items Wear resistance (1000 rpm) Corrosion resistance (72h) Weather resistance (500h) Example 1 No obvious scratches or damage No obvious corrosion spots or damage No noticeable fading or damage Example 2 No obvious scratches or damage No obvious corrosion spots or damage No noticeable fading or damage Example 3 No obvious scratches or damage No obvious corrosion spots or damage No noticeable fading or damage Comparative Example Slight scratches Slight corrosion spots Slightly faded
[0083] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A production process for ultra-white glaze tiles, characterized in that: The following steps are involved: (1) Preparation of base layer: by mass percentage, the raw materials of the base layer include 50% kaolin, 30% quartz sand and 20% feldspar; the raw materials of the base layer are mixed evenly; a hydraulic press is used to press the mixed raw materials to form a base layer body; the pressed body is naturally dried for 24 hours; the dried body is preliminarily sintered to obtain a base tile; (2) Functional layer preparation: The functional layer materials include barium titanate, glass-ceramics containing titanium dioxide, and nanoparticles doped with rare earth elements; Mix barium titanate powder with water to form a slurry, and apply a layer of slurry on the base tile by brushing, with a thickness of 0.5mm; Mix the titanium dioxide-containing glass-ceramic powder with water to form a uniform slurry, and apply it on the bottom layer by scraping to form an intermediate layer with a thickness of 1 mm; The rare earth element-doped nanoparticles were mixed with water to form a uniform slurry, and a surface layer was formed on the intermediate layer by doctor blade coating with a thickness of 0.3 mm; The coated tiles are naturally dried for 24 hours; the dried tiles are subjected to secondary sintering to obtain functional tiles; (3) Preparation of protective layer: The protective layer material includes polyurethane coating; the polyurethane coating is mixed with a diluent; the prepared coating is sprayed evenly on the surface of the tile with a thickness of 0.1 mm using a spray gun; the sprayed tile is dried naturally for 24 hours or accelerated to obtain an ultra-white glazed tile; The titanium dioxide-containing microcrystalline glass is formed by adding titanium dioxide to glass raw materials and performing heat treatment and crystallization at 800-1000° C. The glass raw materials include silicate, alkali metal oxide, calcium magnesium oxide, clarifier and decolorizer; the rare earth element-doped nanoparticles are yttrium-doped aluminum oxide; In the functional layer material, barium titanate accounts for 30% of the total functional layer material mass, and the mass ratio of barium titanate powder to water is 1:0.3 to 1:0.5; microcrystalline glass containing titanium dioxide accounts for 50% of the total functional layer material mass, and the mass ratio of microcrystalline glass powder containing titanium dioxide to water is 1:0.4 to 1:0.6; nanoparticles doped with rare earth elements account for 20% of the total functional layer material mass, and the mass ratio of nanoparticles doped with rare earth elements to water is 1:0.2 to 1:0.
4.
2. The production process of a super white glaze tile according to claim 1, characterized in that: The temperature of the preliminary sintering is 1000-1200° C. and the time is 2 hours.
3. The production process of a super white glaze tile according to claim 1, characterized in that: The particle size of the microcrystalline glass containing titanium dioxide is 5-20 microns.
4. The production process of a super white glaze tile according to claim 1, characterized in that: The secondary sintering is carried out at a temperature of 1100-1300° C. for 3 hours.
5. The production process of a super white glaze tile according to claim 1, characterized in that: The polyurethane coating is a polyurethane varnish, including a polyester polyurethane coating or an aliphatic polyurethane coating.
6. The production process of a super white glaze tile according to claim 1, characterized in that: The accelerated curing temperature is 80° C. and the time is 1 hour.
Citation Information
Patent Citations
Shading ceramic and preparation method thereof
CN105565841A
Opacified glaze and preparation method thereof
CN106698949A